2018
DOI: 10.1021/jacs.8b11257
|View full text |Cite
|
Sign up to set email alerts
|

Welding Metallophthalocyanines into Bimetallic Molecular Meshes for Ultrasensitive, Low-Power Chemiresistive Detection of Gases

Abstract: This paper describes the first demonstration of using a series of isoreticular nickel phthalocyanine- and nickel naphthalocyanine-based bimetallic conductive two-dimensional (2D) metal–organic frameworks (MOFs) as active materials in chemiresistive sensing of gases. Devices achieve exceptional sensitivity at sub-part-per-million (ppm) to part-per-billion (ppb) detection limits toward NH3 (0.31–0.33 ppm), H2S (19–32 ppb), and NO (1.0–1.1 ppb) at low driving voltages (0.01–1.0 V) within 1.5 min of exposure. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
265
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(276 citation statements)
references
References 95 publications
11
265
0
Order By: Relevance
“…As bottom-up fabricated solid materials, MOFs with tunable structures and different properties are mainly defined by the two building blocks: metal centers and organic ligands. Up to now, a series of benzene-, triphenylene-, coronene-, or phthalocyaninederived p-conjugated ligands with different donor atoms (O, S, and N) have been employed for the construction of p-d conjugated MOFs with metal bis(dithiolene), metal catecholates, metal bis(diaminoene) and metal bis(aminothiolato) units (Kambe et al, 2013(Kambe et al, , 2014Huang et al, 2015;Pal et al, 2015;Clough et al, 2017;Dong et al, 2018aDong et al, , 2018bSheberla et al, 2014;Dou et al, 2017;Lahiri et al, 2017;Hmadeh et al, 2012;Park et al, 2018a;Meng et al, 2019;Yang et al, 2019;Zhong et al, 2019). Theoretical studies indicate that replacing sulfur by selenium in a hybrid organic-inorganic semiconductor is predicted to decrease the electronic band gap (Stott et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…As bottom-up fabricated solid materials, MOFs with tunable structures and different properties are mainly defined by the two building blocks: metal centers and organic ligands. Up to now, a series of benzene-, triphenylene-, coronene-, or phthalocyaninederived p-conjugated ligands with different donor atoms (O, S, and N) have been employed for the construction of p-d conjugated MOFs with metal bis(dithiolene), metal catecholates, metal bis(diaminoene) and metal bis(aminothiolato) units (Kambe et al, 2013(Kambe et al, , 2014Huang et al, 2015;Pal et al, 2015;Clough et al, 2017;Dong et al, 2018aDong et al, , 2018bSheberla et al, 2014;Dou et al, 2017;Lahiri et al, 2017;Hmadeh et al, 2012;Park et al, 2018a;Meng et al, 2019;Yang et al, 2019;Zhong et al, 2019). Theoretical studies indicate that replacing sulfur by selenium in a hybrid organic-inorganic semiconductor is predicted to decrease the electronic band gap (Stott et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The good linear log–log plots of response versus concentration (Figure b) are consistent with typical chemiresistive behavior. The theoretical limit of detection (LOD) was calculated to be approximately 0.02 ppm using the linear log–log plot and approximately 0.35 ppm using the linear plot by setting the response equal to 3 RMS (RMS=root‐mean‐square deviation) . These values are comparable with the lowest LOD values of room‐temperature chemiresistors reported to date (see Table S4).…”
Section: Figurementioning
confidence: 56%
“…Response times of 1-30 s represent an order of magnitude improvement over existing MOF strain-based sensors (see ESI Section S17 †). Sub-ppm sensitivity towards a range of VOCs again represents an improvement in strain-based sensing using MOFs, bringing it on par with hard-to-fabricate photonic crystal thin lms, 56 interdigitated electrode devices [57][58][59] and colorimetric sensors, 60 the latter of which was limited in analyte scope to water. Importantly, we have demonstrated that, in principle, any MOF that can be made in NP form 26 can now be employed in strainbased sensing, which allows for an enormous diversity of chemistries and VOC selectivities.…”
Section: Discussionmentioning
confidence: 99%